Comparative Analysis of Credit Systems in the United States, United Kingdom, and Europe: Implications for Academic Mobility and Recognition - Paul (Sr.), Stanley A. V.; Paul (Jr.), Stanley A. V (Integrated Journal for Research in Arts and Humanities, 2024)
This paper presents an in-depth comparative analysis of the credit systems for degree and non-degree programs in the United States (US), United Kingdom (UK), and Europe. It explores the definitions, structures, and functions of these systems, highlighting their differences and implications for academic mobility and recognition. The study concludes with an evaluation of which system is superior and provides recommendations for enhancing global compatibility and effectiveness.